The tangents to the circle ${{x}^{2}}+{{y}^{2}}={{a}^{2}}$ having inclinations $\alpha \text{ and }\beta $ intersect at P. If $\cot \alpha +\cot \beta =0,$ then the locus of P is
(A) x + y = 0
(B) x – y = 0
(C) xy = 0
(D) None of these
Answer
Verified
511.5k+ views
Hint: Use equation of tangent formula from an external point to circle ${{x}^{2}}+{{y}^{2}}={{a}^{2}}$. Form the quadratic and relate the roots with the coefficients of quadratic.
The given equation of circle is,
${{x}^{2}}+{{y}^{2}}={{a}^{2}}$……………….(1)
Two tangents having inclination $\alpha \text{ and }\beta $ which means they are making angles $\alpha \text{ and }\beta $ with x – axis intersecting at P as shown in diagram.
As centre of circle given is (O,O) and radius = a if we compare it with standard equation of circle
${{\left( x-{{x}_{1}} \right)}^{2}}+{{\left( y-{{y}_{1}} \right)}^{2}}={{a}^{2}}$
Where $\left( {{x}_{1}},{{y}_{1}} \right)$ is centre and a is radius.
Let point P is (h, k) of which we have to find locus.
Now, we have two tangents ${{T}_{1}}\text{ and }{{T}_{2}}$ with inclinations $\alpha \text{ and }\beta $. Hence, slopes of tangents ${{T}_{1}}\text{ and }{{T}_{2}}$ be $\tan \alpha \text{ and tan}\beta $ as slope is tan of angle of any line with positive direction of x – axis.
We have given relation from question;
$\cot \alpha +\cot \beta =0$…………………… (2)
As, we know that tangent from any external point of circle ${{x}^{2}}+{{y}^{2}}={{a}^{2}}$ with slope given as m is ;
\[y=mx\pm a\sqrt{{{m}^{2}}+1}\] ………………. (3)
Where m is slope of tangent
a = radius of circle
Let us simplify equation (3) as;
$y-mx=\pm a\sqrt{{{m}^{2}}+1}$
Squaring both sides of above equation;
$\begin{align}
& {{\left( y-mx \right)}^{2}}={{a}^{2}}\left( {{m}^{2}}+1 \right) \\
& {{y}^{2}}+{{m}^{2}}{{x}^{2}}-2myx={{a}^{2}}{{m}^{2}}+{{a}^{2}} \\
\end{align}$
Rewriting the above equation with quadratic in ‘m’, we get;
${{m}^{2}}\left( {{a}^{2}}-{{x}^{2}} \right)+2myx+{{a}^{2}}-{{y}^{2}}=0$ ………………… (4)
Now, we have a quadratic in ‘m’ which means it will have two roots. Let ${{m}_{1}}\text{ and }{{m}_{2}}$ are roots of equation (4).
As tangents are drawn from an external point and only two tangents can be drawn from any external point to circle.
Let these slopes represent tangents ${{T}_{1}}\text{ and }{{T}_{2}}$, which has slope $\tan \alpha \text{ and tan}\beta $.
Hence, ${{m}_{1}}=\tan \alpha ,{{m}_{2}}=\tan \beta $ are roots of equation (4);
As we know, if we have quadratic $A{{x}^{2}}+Bx+C$, then
$\begin{align}
& \text{sum of roots }=\dfrac{-B}{A} \\
& \text{product of roots = }\dfrac{C}{A} \\
\end{align}$
From equation (4), we get;
$\begin{align}
& \tan \alpha +\text{tan}\beta =\dfrac{-2xy}{{{a}^{2}}-{{x}^{2}}} \\
& \tan \alpha +\text{tan}\beta =\dfrac{{{a}^{2}}-{{y}^{2}}}{{{a}^{2}}-{{x}^{2}}} \\
\end{align}$
As, tangents ${{T}_{1}}\text{ and }{{T}_{2}}$ with slopes $\tan \alpha \text{ and tan}\beta $ are intersecting at (h, k). Hence, we can replace (x, y) by (h, k).
Therefore,
$\begin{align}
& \tan \alpha +\text{tan}\beta =\dfrac{-2xy}{{{a}^{2}}-{{h}^{2}}}..............\left( 5 \right) \\
& \tan \alpha +\text{tan}\beta =\dfrac{{{a}^{2}}-{{k}^{2}}}{{{a}^{2}}-{{h}^{2}}}...............\left( 6 \right) \\
\end{align}$
From equation (2), we have;
$\cot \alpha +\cot \beta =0$
We know that $\cot \theta =\dfrac{1}{\tan \theta }$
Hence,
$\begin{align}
& \dfrac{1}{\tan \alpha }+\dfrac{1}{\tan \beta }=0 \\
& \dfrac{\tan \alpha +\tan \beta }{\tan \alpha \tan \beta }=0 \\
& \tan \alpha +\tan \beta =0............\left( 7 \right) \\
\end{align}$
Now, from equation (5), we have;
$\tan \alpha +\tan \beta =\dfrac{-2hk}{{{a}^{2}}-{{h}^{2}}}$ ……………….. (8)
From equation (7) & (8), we get;
$\begin{align}
& \dfrac{-2hk}{{{a}^{2}}-{{h}^{2}}}=0 \\
& hk=0 \\
\end{align}$
Now, replacing (h, k) by (x, y) to get locus;
xy = 0 (Required locus)
Hence, the correct answer is option (C).
Note: Another approach for this question would be that we can suppose point A and B as parametric coordinates. Point A as $\left( a\cos {{\theta }_{1}},b\sin {{\theta }_{1}} \right)$ and point B as $\left( a\cos {{\theta }_{2}},b\sin {{\theta }_{2}} \right)$.
Now, write equation of tangents through A and B as T = 0
Tangents through A and B as
$\begin{align}
& \dfrac{x\cos {{\theta }_{1}}}{a}+\dfrac{y\sin {{\theta }_{1}}}{b}=1 \\
& \dfrac{x\cos {{\theta }_{2}}}{a}+\dfrac{y\sin {{\theta }_{2}}}{b}=1 \\
\end{align}$
Hence, slope of tangents A and B is given as;
$\dfrac{\dfrac{-\cos {{\theta }_{1}}}{a}}{\dfrac{\sin {{\theta }_{1}}}{b}}=\dfrac{-\cos {{\theta }_{1}}}{a}\times \dfrac{b}{\sin {{\theta }_{1}}}=\dfrac{-b\cos {{\theta }_{1}}}{a\sin {{\theta }_{1}}}$
Similarly, tangents through B has
$slope=\dfrac{-b}{a}\dfrac{\cos {{\theta }_{2}}}{\sin {{\theta }_{2}}}$
We have slopes given as $\tan \alpha \text{ and tan}\beta $.
Hence, we have equations
$\begin{align}
& \tan \alpha =\dfrac{-b}{a}\dfrac{\cos {{\theta }_{1}}}{\sin {{\theta }_{1}}}=\dfrac{-b}{a}\cot {{\theta }_{1}} \\
& \tan \beta =\dfrac{-b}{a}\dfrac{\cos {{\theta }_{2}}}{\sin {{\theta }_{2}}}=\dfrac{-b}{a}\cot {{\theta }_{2}} \\
\end{align}$
Now, find intersection point (h, k) by solving equations of tangents written above try to eliminate ${{\theta }_{1}}\And {{\theta }_{2}}$ with the help of given relation $\cot \alpha +\cot \beta =0,$and given above i.e. $\tan \alpha =\dfrac{-b}{a}\cot {{\theta }_{1}},\tan \beta =\dfrac{-b}{a}\cot {{\theta }_{2}}$.
One can go wrong while writing the relations \[\tan \alpha +\tan \beta \]and \[\tan \alpha .\tan \beta \] from the quadratic ${{\left( y-mx \right)}^{2}}={{a}^{2}}\left( {{m}^{2}}+1 \right)$
The given equation of circle is,
${{x}^{2}}+{{y}^{2}}={{a}^{2}}$……………….(1)
Two tangents having inclination $\alpha \text{ and }\beta $ which means they are making angles $\alpha \text{ and }\beta $ with x – axis intersecting at P as shown in diagram.
As centre of circle given is (O,O) and radius = a if we compare it with standard equation of circle
${{\left( x-{{x}_{1}} \right)}^{2}}+{{\left( y-{{y}_{1}} \right)}^{2}}={{a}^{2}}$
Where $\left( {{x}_{1}},{{y}_{1}} \right)$ is centre and a is radius.
Let point P is (h, k) of which we have to find locus.
Now, we have two tangents ${{T}_{1}}\text{ and }{{T}_{2}}$ with inclinations $\alpha \text{ and }\beta $. Hence, slopes of tangents ${{T}_{1}}\text{ and }{{T}_{2}}$ be $\tan \alpha \text{ and tan}\beta $ as slope is tan of angle of any line with positive direction of x – axis.
We have given relation from question;
$\cot \alpha +\cot \beta =0$…………………… (2)
As, we know that tangent from any external point of circle ${{x}^{2}}+{{y}^{2}}={{a}^{2}}$ with slope given as m is ;
\[y=mx\pm a\sqrt{{{m}^{2}}+1}\] ………………. (3)
Where m is slope of tangent
a = radius of circle
Let us simplify equation (3) as;
$y-mx=\pm a\sqrt{{{m}^{2}}+1}$
Squaring both sides of above equation;
$\begin{align}
& {{\left( y-mx \right)}^{2}}={{a}^{2}}\left( {{m}^{2}}+1 \right) \\
& {{y}^{2}}+{{m}^{2}}{{x}^{2}}-2myx={{a}^{2}}{{m}^{2}}+{{a}^{2}} \\
\end{align}$
Rewriting the above equation with quadratic in ‘m’, we get;
${{m}^{2}}\left( {{a}^{2}}-{{x}^{2}} \right)+2myx+{{a}^{2}}-{{y}^{2}}=0$ ………………… (4)
Now, we have a quadratic in ‘m’ which means it will have two roots. Let ${{m}_{1}}\text{ and }{{m}_{2}}$ are roots of equation (4).
As tangents are drawn from an external point and only two tangents can be drawn from any external point to circle.
Let these slopes represent tangents ${{T}_{1}}\text{ and }{{T}_{2}}$, which has slope $\tan \alpha \text{ and tan}\beta $.
Hence, ${{m}_{1}}=\tan \alpha ,{{m}_{2}}=\tan \beta $ are roots of equation (4);
As we know, if we have quadratic $A{{x}^{2}}+Bx+C$, then
$\begin{align}
& \text{sum of roots }=\dfrac{-B}{A} \\
& \text{product of roots = }\dfrac{C}{A} \\
\end{align}$
From equation (4), we get;
$\begin{align}
& \tan \alpha +\text{tan}\beta =\dfrac{-2xy}{{{a}^{2}}-{{x}^{2}}} \\
& \tan \alpha +\text{tan}\beta =\dfrac{{{a}^{2}}-{{y}^{2}}}{{{a}^{2}}-{{x}^{2}}} \\
\end{align}$
As, tangents ${{T}_{1}}\text{ and }{{T}_{2}}$ with slopes $\tan \alpha \text{ and tan}\beta $ are intersecting at (h, k). Hence, we can replace (x, y) by (h, k).
Therefore,
$\begin{align}
& \tan \alpha +\text{tan}\beta =\dfrac{-2xy}{{{a}^{2}}-{{h}^{2}}}..............\left( 5 \right) \\
& \tan \alpha +\text{tan}\beta =\dfrac{{{a}^{2}}-{{k}^{2}}}{{{a}^{2}}-{{h}^{2}}}...............\left( 6 \right) \\
\end{align}$
From equation (2), we have;
$\cot \alpha +\cot \beta =0$
We know that $\cot \theta =\dfrac{1}{\tan \theta }$
Hence,
$\begin{align}
& \dfrac{1}{\tan \alpha }+\dfrac{1}{\tan \beta }=0 \\
& \dfrac{\tan \alpha +\tan \beta }{\tan \alpha \tan \beta }=0 \\
& \tan \alpha +\tan \beta =0............\left( 7 \right) \\
\end{align}$
Now, from equation (5), we have;
$\tan \alpha +\tan \beta =\dfrac{-2hk}{{{a}^{2}}-{{h}^{2}}}$ ……………….. (8)
From equation (7) & (8), we get;
$\begin{align}
& \dfrac{-2hk}{{{a}^{2}}-{{h}^{2}}}=0 \\
& hk=0 \\
\end{align}$
Now, replacing (h, k) by (x, y) to get locus;
xy = 0 (Required locus)
Hence, the correct answer is option (C).
Note: Another approach for this question would be that we can suppose point A and B as parametric coordinates. Point A as $\left( a\cos {{\theta }_{1}},b\sin {{\theta }_{1}} \right)$ and point B as $\left( a\cos {{\theta }_{2}},b\sin {{\theta }_{2}} \right)$.
Now, write equation of tangents through A and B as T = 0
Tangents through A and B as
$\begin{align}
& \dfrac{x\cos {{\theta }_{1}}}{a}+\dfrac{y\sin {{\theta }_{1}}}{b}=1 \\
& \dfrac{x\cos {{\theta }_{2}}}{a}+\dfrac{y\sin {{\theta }_{2}}}{b}=1 \\
\end{align}$
Hence, slope of tangents A and B is given as;
$\dfrac{\dfrac{-\cos {{\theta }_{1}}}{a}}{\dfrac{\sin {{\theta }_{1}}}{b}}=\dfrac{-\cos {{\theta }_{1}}}{a}\times \dfrac{b}{\sin {{\theta }_{1}}}=\dfrac{-b\cos {{\theta }_{1}}}{a\sin {{\theta }_{1}}}$
Similarly, tangents through B has
$slope=\dfrac{-b}{a}\dfrac{\cos {{\theta }_{2}}}{\sin {{\theta }_{2}}}$
We have slopes given as $\tan \alpha \text{ and tan}\beta $.
Hence, we have equations
$\begin{align}
& \tan \alpha =\dfrac{-b}{a}\dfrac{\cos {{\theta }_{1}}}{\sin {{\theta }_{1}}}=\dfrac{-b}{a}\cot {{\theta }_{1}} \\
& \tan \beta =\dfrac{-b}{a}\dfrac{\cos {{\theta }_{2}}}{\sin {{\theta }_{2}}}=\dfrac{-b}{a}\cot {{\theta }_{2}} \\
\end{align}$
Now, find intersection point (h, k) by solving equations of tangents written above try to eliminate ${{\theta }_{1}}\And {{\theta }_{2}}$ with the help of given relation $\cot \alpha +\cot \beta =0,$and given above i.e. $\tan \alpha =\dfrac{-b}{a}\cot {{\theta }_{1}},\tan \beta =\dfrac{-b}{a}\cot {{\theta }_{2}}$.
One can go wrong while writing the relations \[\tan \alpha +\tan \beta \]and \[\tan \alpha .\tan \beta \] from the quadratic ${{\left( y-mx \right)}^{2}}={{a}^{2}}\left( {{m}^{2}}+1 \right)$
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE